Study on Paving the Road to NZEB on Two 18\(^th\) Century Historical Blocks in Lisbon - Carlos Duarte; António Morais (New Approaches in Engineering Research Vol. 6, 2021)
The 1758 Lisbon Pombaline Quarter Reconstruction Plan comprises compact rectangular-shaped residential blocks built with a system that complies solid mass construction elements with a light wooden structure. Considering both constructive and architectural inherent features of the original Pombaline block, it shows the potential to achieve NZEB level if an energy retrofit strategy at a block scale is implemented instead of the usual single building or fraction approach. The retrofit of historic buildings has raised questions regarding intervention’s depth and efficiency. The impact on the built heritage value must be residual or null, while energy-related improvements must be noticeable. This paper intends to analyze and compare the result on energy demand and primary energy consumption of passive, active, and BIST/PV systems packages implementation on two original blocks, with the challenge of minimizing the impact on case studies appearance. A Building Energy Simulation methodology is applied using the whole-of-building dynamic simulation software EnergyPlus. The results show that exterior envelope improvements can reduce up to 50% heating and cooling energy demands increasing thermal comfort at the same time. Finally, a combined VRF/Biomass heating solution displays the best results on primary energy consumption, while photovoltaic and solar thermal systems proved to have an essential role to reach NZEB level performance.